Lecture notes of the discipline "Code of professional ethics of accountants and auditors" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
The text of the lectures includes the main issues related to the theory of the code of professional ethics of accountants and auditors, from the point of view of organizing their activities according to Ukrainian and international standards. The academic discipline is an optional discipline in the block of humanitarian and socio-economic training taught to bachelors in the fourth year. It is intended for the formation of students' theoretical knowledge about the content of standards, in particular the code of professional ethics of accountants and auditors, the regulatory and legal basis of accounting and taxation in Ukraine, the principles on which legal relations are based, the structure and indicators of the assessment of accounting activity.
Keywords: lecture notes; economic activity; finance; management ethics; audit; legal principles; risks